The Irish economy in transition successes, problems, and prospects - Munley, Vincent; Thornton, Robert J. 1943-; Aronson, J. Richard 1937- (Contemporary studies in economic and financial analysis, 2002)
The transformation of Ireland from one of the poorer countries in Western Europe to one of the best performing is one of the most remarkable economic success stories in recent times. The ten papers in this collection were presented at a conference at Lehigh University in March 2001. Written from a broad interdisciplinary perspective, the papers collectively discuss the recent evolution of the Irish economy and the factors responsible. They also analyze the problems that rapid growth has generated and the consequent domestic policy challenges in such areas as infrastructure, the environment, education, and social welfare.